How Freelancers Experience Online Labor Marketplaces during a Pandemic - Gerber, Elizabeth M.; Foong, Eureka (2020)
ABSTRACT During the global pandemic induced economic downturn, the number of people who do freelance work is rapidly increasing. With increased participation, it is important to understand how freelancers are experiencing the online labor marketplace. To shed light on this current phenomenon, we survey 392 U.S. freelancers (both new and experienced) to understand their initial perceptions of the experience. We uncover both negative and positive impacts on freelancers which include more competition, less time to complete work, change in pay, and risk aversion, as well as more time to complete work, new jobs, and more time to attract clients. Future work will explore the impact based on gender, age, work experience, geographic demographics, and wage setting. To better support the rapidly evolving gig economy during the pandemic, we encourage longitudinal evaluation of freelancers in online labor marketplaces. Keywords future of work; online labor marketplaces; freelance work; economic downturn ABOUT THE AUTHOR/S Elizabeth M. Gerber Northwestern University egerber@northwestern.edu Elizabeth Gerber is an Associate Professor of Design and Co-Founder and Co-Director of the Human Computer Interaction and Design Center at Northwestern University. More info at www.lizgerber.com. Eureka Foong Northwestern University eureka@u.northwestern.edu Eureka Foong is a PhD student in the Technology and Social Behavior Program at Northwestern University. More info at www.eurekafoong.com. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).